Padrões da área do xilema ativo em espécies florestais amazônicas na região de Manaus (Am) - Aparecido, Luiza Maria Teóphilo (Instituto Nacional de Pesquisas da Amazônia - INPA, 2014)
Hydrological processes in forest stands are mainly influenced by the stand forming plant species and their physiological characteristics. Distinct water use patterns of certain species can lead to limitation in forest management practices. Most tropical studies determining the water use pattern of forest plant species were conducted almost exclusively outside Brazil. Thus, the purpose of this thesis was to obtain sapwood area patterns through dye immersions in forest species near the city of Manaus – Amazonas. The data of sap wood area was associated with the ecology of the collected tree species and açai palm individuals (Euterpe precatoria), wood anatomy, diameter at breast height (DBH), height and volume. Allometric models to determine sapwood area were applied. Another section of this thesis focused on analyzing hydraulic conductivity at different heights of açai palms and hydraulic conductivity between different tree species. Finally, compare results obtained between trees and palms. Data were collected at the ZF-2 experimental field site on km 18 of the vicinal road. 34 sample trees were chosen randomly in an area of approximately 6 ha. Tree height was measured after cutting the tree. Stem sections of the harvested trees were taken to the laboratory to be immersed in indigo carmine dye solution until coloring was apparent on the upper side of the log. The colored cross section was assumed to be the conducting tissue of the sapwood and was measured along with diameter. Species were identified through anatomical wood characteristics. Vessel diameter, frequency and length were measured in a specialized wood laboratory. Sapwood patterns differed between and within species although all were diffuse porous. The allometric model was obtained through linear and non-linear regressions. The best relationship and model fit was obtained between sapwood area and DBH with a non-linear model. The null relationship and worse model fil was with vessel frequency that didn’t present any apparent influence over sapwood area. Model fits didn’t present high statistical parameters, but excluding vessel diameter and frequency, all relationships were positive and conclusive. These low statistical parameters can be explained through certain species characteristics, microclimate and ecological factors. Hydraulic conductivity between the sampled trees was very distinct with values varying from 0.09 to 24 kg m-1s MPa-1. These differences were also explained through species autoecology and microclimate. Ten açai palms were collected near the same study area as trees and were submitted to the same coloring process and wood anatomy analysis. Palms presented same sapwood pattern within and between species. Hydraulic conductivity was different in the heights analyzed. Hydraulic conductivity in the base of the crown was higher than in the base of the trunk, due to the high density of vessels in a small cross-section or sapwood area in this height. Palm trees also presented a positive relationship with DBH. When comparing trees and palms, we observed that trees and palms share the positive relationship with DBH, but presented different sapwood patterns and hydraulic conductivity values. Thus, this study showed how species present different characteristics that can influence water transport, but have common variables that can maintain the ecosystem balance they grow and assist in the estimation of forest stand transpiration.
Keywords: Ecofisiologia florestal; Palmeiras; Área do xilema